Successful treatment of extensive cerebral venous sinus thrombosis using a combined approach with Penumbra aspiration system and Solitaire FR retrieval device. (10th September 2013) - Raychev, Radoslav; Tateshima, Satoshi; Rastogi, Sachin; Balgude, Amit; Yafeh, Banafsheh; Saver, Jeffrey L; Vespa, Paul M; Buitrago, Manuel; Duckwiler, Gary
Abstract : We present a young woman with rapidly progressive neurologic decline in the setting of malignant cerebral edema due to extensive superior sagittal sinus thrombosis and cortical venous thrombosis despite intravenous heparin administration. Complete revascularization of the occluded sinus was achieved using suction thrombectomy with the 5 max Penumbra catheter in combination with the Solitaire FR clot retrieval device. The successful endovascular treatment halted the progression of her cerebral edema, and the patient eventually had an excellent recovery after prolonged intensive medical therapy. To our knowledge, this is the first reported case describing such a combined mechanical approach for cerebral venous sinus thrombosis. The clot retrieval properties of the Solitaire device combined with direct aspiration via the newest generation Penumbra catheters may allow more rapid, safe and efficient revascularization than all previously reported endovascular treatments for this potentially devastating condition.